The role and nature of consent in government administrative data. Issue 2 (December 2018) - Sexton, Anna; Shepherd, Elizabeth; Duke-Williams, Oliver; Eveleigh, Alexandra
This article draws on research undertaken by the authors as part of the Administrative Data Research Centre in England (ADRC-E). Between 2014 and 2017, we conducted four case studies on government administrative data for education, transport, energy and health. The purpose of the research was to examine stakeholder perspectives about the sharing, linking and re-use (secondary use) of government administrative data. In relation to the role and nature of consent given by data subjects for re-use, our study revealed significant variations in data provider and researcher attitudes. Although our study setting was England, we believe that the findings have wider resonance. Our analysis identified six factors which might account for the variations around consent: the specificities of the legislative framework governing the collection and processing of particular data; the type of data being collected and the relational context in which it is created; the broader information governance framework in which the data resides; the creating organization's approach to data release; the relative levels of risk aversity within the creating organization; and public perceptions and social attitudes. In conclusion, we consider whether consent is still the best mechanism available for data re-use, or whether a social contract model of data sharing should be developed.